Adverse clinical outcomes and associated factors among older adults undergoing hemodialysis in Brazil: A single-center experience. - Laurisson Albuquerque da Costa; Andre Faro; Thaisa Leite Valverde; Somkanya Tungsanga; Aminu K Bello (PLoS ONE)
Introduction In the last decade, there has been an increase in the number of older adults diagnosed with kidney failure in Brazil. Anecdotal reports suggest that older adults receiving hemodialysis (HD) face a higher risk of adverse outcomes. This study aims to investigate adverse clinical outcomes and associated factors among adults over age 60 who received chronic HD at a single center in northeastern Brazil. Methodology We conducted a retrospective cohort of older adults undergoing HD at a center in Aracaju, Sergipe, Brazil, from October 1, 2019 to March 1, 2024. Multivariable Cox regression analysis was performed to examine the associations with various risk factors for all-cause mortality. A binomial logistic regression model was leveraged for Major Cardiovascular Events (MACE) and all-cause hospitalization. Results Among the 950 adults, 392 individuals over age 60 were included in our sample (median age: 68.5 years, IQR: 64-75; male: 63%). Diabetes was the leading cause of kidney failure. The total number of deaths was 157 (40.1%), primarily due to infection (n = 60, 38.2%). Multivariable analysis indicated that increased age was independently associated with all-cause mortality [HR = 1.07 (1.02-1.09), p = 0.001], while fistula use was associated with reduced mortality risk [HR = 0.36 (0.19-0.68), p = 0.02]. Although hospitalization rate increased with age, this relationship is not statistically significant. Health insurance and hypertension increased hospitalization risk, whereas fistula use was protective. Previous history of cardiovascular disease (CVD) and low serum albumin were associated with MACE. The bloodstream infection rate was 0.18 episode/patient-year, predominantly due to gram-positive organisms, with coagulase-negative Staphylococcus being the most common. Conclusion Among patients undergoing HD, older age is associated with a high risk of all-cause mortality. Fistula use appeared to be protective against all-cause mortality and hospitalization. Well-designed prospective studies are needed to clarify factors impacting adverse outcomes among older dialysis patients in Brazil.